Factors Influencing the Disparity of Schools in the Urban Sector of Sri Lanka: A Case Study in Wattegama Urban Council - H. N. K. Galahitiyawa (Partners Universal International Research Journal, 2022)
Although Sri Lanka has been providing Free Education since 1939, still access to a quality education throughout a child’s schooling years remains a challenge for children in certain communities in Sri Lanka. Disparity of Education in Sri Lanka is merely not the unequal distribution of resources, but also a result of failing access to quality education. However, the disparity of education in Sri Lanka is not recent in origin. It traces back to the British Colonization where the Formal Education was formed. It was not surreptitious that the disparity of education in Sri Lanka led to a greater trail with the establishments of education policies throughout the history. The weak points of the Kannangara Free Education Policy (1945), Language Policy in 1956, establishments of curriculum development centres in 1960s, introduction of Grade V Scholarship Examination in 1948 and emergence of private schools in 1977 have strengthened the disparity of education in Sri Lanka. Majority believed the fact that, the disparity of schools remains in the rural and estate sectors in Sri Lanka compared to the urban sector. Urban sector is considered a place with better facilities and higher competition compared to the estate and the rural sectors in Sri Lanka, yet the Disparity of Education within the Urban sector was neglected. Even though a serious consideration has not been paid into this topic in the academia, this problem still exists in the urban sectors of Sri Lanka. It is questionable that why two government schools located in the same vicinity gets different demand from the parents. This study mainly focus on investigating the factors which contribute to the disparities of the schools in the Urban Sector by taking the Wattegama Urban sector located in the central province in Sri Lanka as a case study.